Immunophenotypic Analysis of Platelets by Flow Cytometry. Issue 6 (25th June 2021) - Spurgeon, Benjamin E.J.; Linden, Matthew D.; Michelson, Alan D.; Frelinger, Andrew L.
Abstract: Platelets are small but very abundant blood cells that play a key role in hemostasis, contributing to thrombus formation at sites of injury. The ability of platelets to perform this function, as well as functions in immunity and inflammation, is dependent on the presence of cell surface glycoproteins and changes in their quantity and conformation after platelet stimulation. In this article, we describe the characterization of platelet surface markers and platelet function using platelet‐specific fluorescent probes and flow cytometry. Unlike traditional platelet tests, immunophenotypic analysis of platelets by flow cytometry allows the analysis of platelet function in samples with very low platelet counts as often encountered in clinical situations. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Immunophenotyping of platelet surface receptors Alternate Protocol : Fix‐first method for immunophenotyping of platelet surface receptors Basic Protocol 2 : Determination of platelet activation using P‐selectin expression and/or PAC1 binding Basic Protocol 3 : Determination of procoagulant platelets using annexin V binding or antibodies specific for coagulation factor V/Va or X/Xa Support Protocol : Preparation of isolated platelets